ANALISIS KINERJA KEUANGAN PADA PT. AGUNG PODOMORO LAND TBK DAN PT. BUKIT ULUWATU VILLA Tbk (Study kasus berdasarkan laporan keuangan selama 2016-2019) - Nuzulul Qurnain (Masyrif : Jurnal Ekonomi, Bisnis dan Manajemen, 2022)
The purpose of this study is to determine the financial performance of PT. Agung Podomoro Land Tbk and PT. Bukit Uluwatu Villa Tbk from 2016 to 2019 in terms of the financial ratios of Liquidity, Solvency and Profitability. The analytical tool used is in the form of financial ratios consisting of Liquidity, Solvency, and Profitability ratios. Research data is secondary data obtained from financial reports. The research method uses a comparative descriptive method. Based on the analysis results obtained from 2016 to 2019 namely the liquidity ratio for PT. APL has fluctuated, namely the Current ratio from 2016 - 2019, 1.07, 1.31, 1.05 and 1.66, while PT. BUV decreased to 1.15, 0.48, 0.35 and 0.28. For cash ratio PT. APL fluctuated, namely 0.15, 0.32, 0.11 and 0.17, while PT. BUV decreased by 0.19, 0.03, 0.02 and 0.01, the higher the current ratio, quick ratio, and cash ratio, the greater the company's ability to pay off its debts. The solvency ratio for PT. APL Debt to Asset Ratio decreased, namely 0.61, 0.60, 0.59, 0.56, while PT. BUV fluctuated, namely 0.42, 048, 0.44, and 0.47. For Debt to Equity Ratio PT. APL decreased by 1.58, 1.50, 1.44 and 1.30, while PT. BUV has fluctuated, namely 0.74, 0.92, 0.77 and 0.88, so this situation is detrimental for the company, because the larger the loan amount used. Where these results are in accordance with the results of previous studies that examined these two companies. However, the amount of own capital that is used as collateral for long-term debt and the company's ability to pay PT. Agung Podomoro Land Tbk is higher than PT. Bukit Uluwatu Villa Tbk.